How Effective is Learning Style Material with E-Modules During the COVID-19 Pandemic? - Dewa Ayu Made Manu Okta Priantini; Ni Luh Gede Karang Widiastuti (Jurnal Ilmiah Sekolah Dasar, 2021)
The problem behind this research was the lack of learning resources for students in science subjects so that learning outcomes are less than optimal. This research was a research and development (research and development). The research trial subjects were fourth grade students. The data collection instrument used was in the form of an evaluation sheet (questionnaire). The data analysis used qualitative descriptive analysis and quantitative descriptive analysis. The results of the assessment of the e-module product were carried out based on six aspects, namely: content aspects of the field of study / with a percentage of achievement level of 86.00% with a predicate worthy; In terms of the learning design aspect, the percentage of achievement level is 87.60%, predicate worthy; In terms of the learning media aspect with the achievement level percentage of 89.00%, the predicate is feasible; in terms of the individual trial aspect, with the percentage level of achievement of 92.50% the predicate is very feasible; small group trial, with the percentage of achievement level of 94.50%, the predicate is very feasible, and in terms of the field trial aspect, the percentage of the achievement level is 95.50%, the predicate is very feasible. Thus the product in the form of e-module has a good level of validity and is suitable for use in the learning process on the subject force material of science subjects.